ANALISIS YURIDIS TERHADAP PUTUSAN KASASI NOMOR 365K/PID/2012 DAN PUTUSAN PENINJAUAN KEMBALI NOMOR 79PK/PID/2013 TENTANG PERBUATAN YANG KARENA KEALPAAN DOKTER MENYEBABKAN MATINYA ORANG LAIN - Harahap, Radar Oloan; Deliana, Evi; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Malapraltik is an error that occurs in a medical action, which error isdone accidentally. If an incident occurs the doctor does not do work inaccordance with professional standards and professional operational standardsdue to the condition of the patient who must be taken medical action this will beproblematic if the patient experiences disability and death. Dr. Case example AyuAyu Saseary Prawani, Dr. Hendry Simajuntak and Dr.Hendy Siagian wasconvicted for not acting according to professional standards and standardoperating procedures due to the condition of patients who need help in anemergency. Based on this understanding the author of this thesis formulates twoformulations of the problem, namely: first what is the basis for consideration ofthe judge Cassation Number 365K / Pid / 2012 and consideration of judgesRevisiting Number 79PK / Pid / 2013 in determining the verdict, Secondemergency without giving informed consent to the patient resulting in death.This type of research can be classified in normative juridical research,because this research is conducted by examining secondary data and approachesto law, this normative study examines legal synchronization to reveal reality, tothe extent that certain laws are in a vertical, harmonious manner horizontallywhen it comes to laws that are in the same field. The data sources used are,primary data, secondary data, tertiary data, data collection techniques in thisstudy are normative juridical, the data used is library research.In the results of the discussion in the writing of the thesis is Firstreviewing how the interpretation of the judge in deciding the case andconsideration of the judge Cassation and consideration of the Review of the Caseof Dr. Dewa Ayu Saseary Prawani, Dr. Hendry Simanjuntak and Dr. HendySiagian. Secondly, a review of the Law needs to be made regarding Informedconsent, which is necessary to reduce or eliminate malpractice.Keywords: Medical Malpractice, Forgiveness, Criminal Responsibility,Decision, Legal Certainty